Zooming into Engagement: Exploring Cognitive, Behavioral, and Emotional Dynamics in EFL Writing Classes - Anggrainy, Septy (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
The transition to online learning during the COVID-19 pandemic brought significant challenges to maintaining student engagement, particularly in video conferencing-based EFL writing classes. While prior research has highlighted the potential of platforms like Zoom for synchronous learning, studies focusing on the dimensions of cognitive, behavioral, and emotional engagement in writing courses remain limited. This study aims to measure the levels of student engagement in video conferencing-based EFL writing classes and identify strategies to enhance engagement across these dimensions. Employing a mixed-method approach, the study involved 40 English Education undergraduate students at UIN Raden Intan Lampung, selected through purposive sampling. Quantitative data were collected using a questionnaire with 30 items measuring engagement dimensions, distributed via Google Forms. Qualitative data were obtained from semi-structured face-to-face interviews with 10 purposively selected participants. The questionnaire data were analyzed using SPSS for descriptive and inferential statistics, while thematic analysis was applied to the interview transcripts. The findings reveal high levels of cognitive engagement, with students actively participating in writing tasks facilitated by Zoom’s interactive features. However, behavioral engagement was moderate due to external challenges like connectivity issues and environmental distractions. Emotional engagement ranged from moderate to high, with students appreciating the platform's flexibility but occasionally experiencing feelings of isolation. The study highlights the need for integrating gamification, structured feedback, and hybrid learning models to address these challenges.